School Time and Democratic Management: Mais Educação Program and the IDEB in search of quality of education - Elisangela da Silva Bernado; Ana Carolina Christovão (Universidade Federal do Rio Grande do Sul, 2016)
This article aims to investigate how the Mais Educação Program has been developed in Rio de Janeiro's public schools, specifically the aspects of full-time education and democratic management. This is an exploratory study combining quantitative and qualitative approaches, by means of a survey of educational data and interviews with school managers, in order to observe possible impacts on the quality of education.